EXPERIMENTAL RESEARCH ON WELDING STRAIN CONCENTRATION OF Y-JOINT WITH DIC TECHNOLOGY - CHEN GuoQiang; PENG WenJing; WU AnRu (Jixie qiangdu)
Bending deflection is the main form of welding deformation,which is liable to occur in the Y-joint. Therefore,this paper investigated the strain distribution of Y-joint under the tensile test with digital image correlation（ DIC）. The study results showed that the strain distribution on the groove angle bisector is in approximate linear. On the inner side of groove angle bisector,the compressive strain is the largest,and on the outside of groove angle bisector the largest strain is tensile strain. The strain concentration is occurred in the groove area,however,the strain distribution curves are different with the areas. In order to reduce the strain concentration,the welding specimen was treated by annealing and the results showed that the strain distribution is more uniform compared with no annealing processing.